Green Synthesis of CuO-Doped Fe₃O₄ for Degradation of Crystal Violet Dye: RSM-Based Optimization - Ady Mara; Fahma Riyanti; Desnelli; Poedji Loekitowati Hariani (Universitas PGRI Madiun, 2026)
The limitations of CuO photocatalyst include high electron–hole recombination and low charge-transfer efficiency. In this context, doping with Fe3O4 is used to form a heterojunction, which enhances charge separation, increases electron transfer, and imparts magnetic properties for easy separation and reuse of the catalyst. Therefore, this study aimed to synthesize a biphasic CuO/Fe₃O₄ composite using Rhodomyrtus tomentosa leaf extract as a green reducing agent, and evaluate the performance as a photocatalyst for the degradation of Crystal Violet Dye (CVD). Structural, morphological, optical, and magnetic properties were characterized using X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM–EDX), UV–Vis diffuse reflectance spectroscopy (DRS), and vibrating sample magnetometer (VSM). XRD patterns confirmed the coexistence of CuO and Fe₃O₄ phases, indicating successful composite formation. VSM analysis reported that the composite had magnetic properties with a saturation magnetization and band gap values of 46.92 emu/g and 1.63 eV, respectively. Process optimization was conducted using Response Surface Methodology (RSM) based on Central Composite Design (CCD). The results showed that the quadratic model was the most appropriate and statistically significant model, indicated by a p-value < 0.05 with a coefficient of determination (R2) of 0.9953. In addition, optimization of the degradation process led to CVD degradation efficiency of 98.73% under optimal conditions of initial concentration of 25.4 mg/L, pH 9.5, and irradiation time of 39.4 min with a visible-light radiation source. The composite also reported good reusability, retaining 92.11% of degradation efficiency after five cycles, confirming the potential as a magnetically recoverable, environmentally sustainable photocatalyst for wastewater treatment applications.